Analisis Pemeriksaan Persediaan Barang dan Pembelian Terhadap Laba Kotor Pada PT Jaya Marta Sentosa Periode 2020-2021 - Fatimah, Tania; Sinambela, Tony R; Nurfai (Mulia Pratama, 2024)
Given the breadth of problems in this study, the author limits the scope of the problem so that the research is more focused and does not deviate from the problem, limiting the problem to the Inventory Inspection, Purchasing, and Gross Profit. How is the inventory check and purchase program at PT. Jaya Marta Sentosa. In the results of the 2020 inventory inspection hospitalization activity, there was a difference of less than Rp. -458,229,870,- In the results of the 2021 inventory inspection hospitalization activity, there was a difference of more than Rp. 667,290,080,- In the 2020 goods purchase table, there were 12 types of goods with an initial amount of 79,168 units, 106,561 units of incoming (buy) inventory, 106,440 units of outgoing inventory (sold) and a final number of 79,307 units with a total of 79,307 units value of Rp. 11.427.517.320,- In the 2021 goods purchase table, there are 12 types of goods with an initial amount of 54,646 units, 111,060 units of incoming (buy) inventory, 100,586 units of outgoing inventory and a final amount of 65,120 units with a total value of Rp. 10,808,651,120,- In 2020 there is a difference in the inventory of goods of Rp. -458,229,870, - caused by the use of inventory items, while in 2021 there was a difference of more than Rp. 667,290,080,- due to the repurchase of inventory. In 2020, adjustments have been made to the Income Statement with an initial nominal profit of Rp. 551,192,786, - after adjustment, the final value of Profit is Rp. 92,962,916,-. Meanwhile, in 2021, the Income Statement with the initial nominal profit is Rp. 929,646,182, - after adjustment, the final value of Profit is Rp. 262,356,102,-.